Molecular detection of genotypes and subtypes of Cryptosporidium infection in diarrheic calves, lambs, and goat kids from Turkey. (December 2020) - Kabir, Mohammad Hazzaz Bin; Ceylan, Onur; Ceylan, Ceylan; Shehata, Ayman Ahmed; Bando, Hironori; Essa, Mohamed Ibrahim; Xuan, Xuenan; Sevinc, Ferda; Kato, Kentaro
Abstract: The studies on Cryptosporidium infections of animals in Turkey mostly rely on microscopic observation. Few data are available regarding the prevalence of Cryptosporidium genotypes and subtypes infection. The aim of this study is to analyse the detection of Cryptosporidium genotypes and subtypes from young ruminants. A total of 415 diarrheic fecal specimens from young ruminants were examined for the Cryptosporidium detection by use of nested PCR of the small subunit ribosomal RNA (SSU rRNA) gene and the highly polymorphic 60 kDa glycoprotein (gp60) gene followed by sequence analyses. The results of this study revealed that 25.6% (106 of 415) of the specimens were positive for Cryptosporidium spp. infection. We identified 27.4% (91/333), 19.4% (13/67), and 13.4% (2/15) of positivity in calves, lambs and goat kids, respectively. Genotyping of the SSU rRNA indicated that almost all positive specimens were of C. parvum, except for one calf which was of C. bovis . Sequence analysis of the gp60 gene revealed the most common zoonotic subtypes (IIa and IId) of C. parvum. We detected 11 subtypes (IIaA11G2R1, IIaA11G3R1, IIaA12G3R1, IIaA13G2R1, IIaA13G4R1, IIaA14G1R1, IIaA14G3R1, IIaA15G2R1, IIdA16G1, IIdA18G1, IIdA22G1); three of them (IIaA12G3R1, IIaA11G3R1 and IIaA13G4R1) was novel subtypes found in calves and lambs. Additionally, three subtypes (IIaA11G2R1, IIaA14G3R1, and IIdA16G1) were detected in young ruminants for the first time in Turkey. These results indicate the high infection of Cryptosporidium in Turkey and propose that young ruminants are likely a major reservoir of C. parvum and a potential source of zoonotic transmission. Graphical abstract: Unlabelled Image Highlights: High occurrence of Cryptosporidium parvum infection in calves, lambs, and goat kids in Turkey. Identified 11 subtypes, three of them (IIaA12G3R1, IIaA11G3R1 and IIaA13G4R1) was novel subtypes. Three subtypes (IIaA11G2R1, IIaA14G3R1, and IIdA16G1) were detected for the first time in Turkey.